Studies of the MuSK system using molecular dynamics simulations - Buyan, A (2015)
Formation and maintenance of neuromuscular junctions, as well as signalling from the nerve to the muscle, depends on the concerted action of a number of membrane proteins. Muscle-Specific Kinase (MuSK) and Downstream-of-Kinase 7 (Dok7) are key players in these processes. MuSK acts as the central component in the complexes responsible for nervemuscle communication. Dok7 then regulates full activation of MuSK. Despite available structural data for these proteins, the structure of the overall Dok7/MuSK complex in a cell membrane remains elusive. In this thesis, a multi scale molecular simulation approach (combining coarsegrained and atomistic simulations) was used to study the formation of the Dok7/MuSK/membrane complex. Three major insights into this process were obtained. Firstly, dimerisation of the transmembrane helix of MuSK is mediated by a small-x-x-x-small amino acid motif, and it is not affected significantly by the addition of anionic lipids or unstructured extensions on each end of the helices. Secondly, Dok7 interacts with PIP-containing bilayers via a positive patch on its pleckstrin-homology (PH) domain. Thirdly, it is shown that MuSK's behaviour in a complex model membrane is potentially influenced by the presence of Dok7. Taken together, these results allow formulation of a defined model of the structure and mechanism of MuSK in a model membrane.